1984
DOI: 10.1055/s-2008-1036304
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Kurzzeitprophylaxe der Puerperalinfektionen nach Kaiserschnitt mit Metronidazol

Abstract: A prospective randomised placebo-controlled clinical study showed that it was not possible to reduce the infectious morbidity following Caesarean section by one perioperative intravenous infusion of 500 mg metronidazole. Of all the 219 patients the endometritis rate was 6%, the wound infection rate 6% and the puerperal sepsis rate 2%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Often a repeat section had been classified as elective by the study authors, but it was not always evident that all of these women were indeed not in labor and often the duration of membrane rupture was unclear. Fifty-two studies (N = 7765) were classified as undefined type of cesarean section (Adeleye 1981; Allen 1972; Apuzzio 1982; Bibi 1994; Bilgin 1998; Bourgeois 1985; Carl 2000; Chan 1989; Cormier 1989; De Boer 1989; Dillon 1981; Duff 1980; Engel 1984; Escobedo 1991; Gall 1979; Ganesh 1986; Gerstner 1980; Gibbs 1972; Gibbs 1973; Gordon 1979; Gummerus 1984; Hager 1983; Hagglund 1989; Ismail 1990; Jaffe 1985; Karhunen 1985; Kellum 1985; Kreutner 1978; Kristensen 1990; Lapas 1988; Levin 1983; Lewis 1990; Mallaret 1990; McCowan 1980; Miller 1968; Moro 1974; Morrison 1973; Ng 1992; Padilla 1983; Phelan 1979; Polk 1982; Reckel 1985; Rehu 1980; Roex 1986; Rudd 1981; Saltzman 1985; Stage 1982; Stiver 1983; Tully 1983; Turner 1990; Walss Rodriguez 1990; Yip 1997). One study reported both elective and emergency cesarean sections; the emergency sections, however, did not meet our definition of non-elective and these have been classified as “undefined” (Rouzi 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often a repeat section had been classified as elective by the study authors, but it was not always evident that all of these women were indeed not in labor and often the duration of membrane rupture was unclear. Fifty-two studies (N = 7765) were classified as undefined type of cesarean section (Adeleye 1981; Allen 1972; Apuzzio 1982; Bibi 1994; Bilgin 1998; Bourgeois 1985; Carl 2000; Chan 1989; Cormier 1989; De Boer 1989; Dillon 1981; Duff 1980; Engel 1984; Escobedo 1991; Gall 1979; Ganesh 1986; Gerstner 1980; Gibbs 1972; Gibbs 1973; Gordon 1979; Gummerus 1984; Hager 1983; Hagglund 1989; Ismail 1990; Jaffe 1985; Karhunen 1985; Kellum 1985; Kreutner 1978; Kristensen 1990; Lapas 1988; Levin 1983; Lewis 1990; Mallaret 1990; McCowan 1980; Miller 1968; Moro 1974; Morrison 1973; Ng 1992; Padilla 1983; Phelan 1979; Polk 1982; Reckel 1985; Rehu 1980; Roex 1986; Rudd 1981; Saltzman 1985; Stage 1982; Stiver 1983; Tully 1983; Turner 1990; Walss Rodriguez 1990; Yip 1997). One study reported both elective and emergency cesarean sections; the emergency sections, however, did not meet our definition of non-elective and these have been classified as “undefined” (Rouzi 2000).…”
Section: Resultsmentioning
confidence: 99%
“…This was variably described as “pre-operatively”, “with induction of anaesthesia” or “before clamping of the cord”. In 43 studies (N = 7284) the antibiotic was administered at or after cord clamping (Apuzzio 1982; Bagratee 2001; Bourgeois 1985; Bilgin 1998; Carl 2000; Conover 1984; Cormier 1989; Dashow 1986; D’Angelo 1980; Dillon 1981; Elliott 1986; Engel 1984; Escobedo 1991; Fugere 1983; Ganesh 1986; Gibbs 1981; Gummerus 1984; Hager 1983; Harger 1981; Hawrylyshyn 1983; Ismail 1990; Jakobi 1994; Karhunen 1985; Kellum 1985; Kristensen 1990; Leonetti 1989; Levin 1983; Lewis 1990; Mallaret 1990; Polk 1982; Rizk 1998; Roex 1986; Rouzi 2000; Rudd 1981; Ruiz-Moreno 1991; Saltzman 1985; Shah 1998; Stiver 1983; Tully 1983; Walss Rodriguez 1990; Wong 1978; Wu 1991; Young 1983). Included in this group were studies where irrigation of the peritoneal or uterine cavity with an antibiotic containing solution was compared with either saline irrigation or no irrigation (Bourgeois 1985; Carl 2000; Conover 1984; Dashow 1986; Elliott 1986; Kellum 1985; Levin 1983; Lewis 1990; Rudd 1981; Wu 1991).…”
Section: Resultsmentioning
confidence: 99%